Study on Determination Method of Inter Well Pumping System for Liquid Supply Shortage Well - LİANG, Xingyuan; LEİ , Jiang; LU, Yi (International Journal of Computational and Experimental Science and Engineering, 2020)
In the grim situation of low oil prices, the oil exploration and production companies have to reduce costs and increase benefits. The wells with deficient-liquid supply account for 20%-30% for all production wells, the proportion of the oil field in the long production time is greater. Intermittent production is an effective way to reduce the cost and increase the efficiency of the oil supply shortage. The purpose of intermittent production is to increase production and reduce cost. The key is determining a reasonable intermittent pumping system, which means develop a proper close time and open time. The author studies the dynamic liquid level variation, uses electrical power curve to solve the dynamometer card, through changing in the diagram to determine the dynamic liquid level decline rule, and then get the time of open well; through analyzing the relationship between the inflow performance of oil wells and the submergence to determine the close time.